EDITORIAL: New Horizon for Industrial Engineering and Management - Marjanovic, Ugljesa (International Journal of Industrial Engineering and Management, 2021)
Another volume is behind us, with 24 papers discussing exciting topics in industrial engineering and management. The fourth Industrial Revolution has brought disruptive changes in academic research and industrial practices in manufacturing. The traditional methods of production and their supply chains affected by the latest technologies such as artificial intelligence will lead to more resilient, sustainable, and smart production. Manufacturing companies need to find an appropriate response to increase efficiency, reduce costs, improve agility and flexibility, and upgrade the responsiveness and resilience of their production operations. Indeed, the digital transformation of production has brought a new horizon, and the International Journal of Industrial Engineering and Management (IJIEM) will continue to serve researchers and practitioners in the industrial engineering, manufacturing engineering, and management fields.